Implementasi Pembelajaran Fiqh Dalam Meningkatkan Motivasi Sholat Berjamaah Siswa Diniyah Takmiliyah Awwaliyah Al-Inshof Cibadak Lebak - Setiawan, Iwan (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2015)
In various Islamic education institutions, especially the Diniyah Takmiliyah Awaliyah (DTA) school, there are still many inequalities in the implementation of Islamic curriculum development especially in the subject of fiqh theory and practice fiqh. This is worrying about giving birth to alumni who do not understand the importance of learning fiqh theory and practice. On the other hand the students when at home each received less attention in the field of amaliyah fiqh practice. Another worrying aspect is the existence of an environment that is far from religious values. So that the complexity of the students' crisis which is not in accordance with Islamic law will actually occur.The purpose of this study was to determine the implementation of the implementation of fiqh learning in the Al-Inshof DTA in increasing the motivation of prayer in the congregation of students. Based on the analysis of data from the research results it can be seen that there is a significant positive correlation between fiqh learning and an increase in the implementation of fardu prayer for students in the DTA Al-Inshof Cibadak. In this study carried out using descriptive qualitative research methods, through collecting data with interviews and by direct observation to the field to obtain valid data and facts.The implementation of jurisprudence learning organized by the Al-Inshof Cibadak DTA has considerable positive implications for the motives of prayer in congregation of DTA students. On the other hand the Al-Inshof Cibadak DTA has steps taken to support the learning of jurisprudence in motivating students in performing prayer together as follows: First, provide guidance and supervision to the teacher to master fiqh material about the prayer chapter. Second, supervise and monitor the students so that they know how far the prayer chapter material is absorbed by them. Third, giving examples of good and true worship practices according to the rules of jurisprudence. Fourth, carry out prayers simultaneously both by the teacher and by the students.Di berbagai lembaga pendidikan Islam khusunya sekolah Diniyah Takmiliyah Awaliyah (DTA) masih banyak dijumpai berbagai ketimpangan dalam pelaksanaan pengangajaran kurikulum Islam khusunya pelajaran fiqh teori dan fiqh praktek.  Hal ini dikuwatirkan akan melahirkan para alumni yang kurang memahami pentingnya belajar fiqh teori dan praktek.   Disisi lain para siswa tatkala dirumah masing-masing kurang mendapatkan perhatian dibidang pengamalan fiqh amaliyah.  Aspek lain yang mengkuwatirkan adalah keberadaan lingkungan yang jauh dari nilai-nilai agamis.  Sehingga kekuwatiran krisis anak didik yang tidak sesuai dengan syariat Islam  akan benar-benar terjadi.Tujuan dari penelitian ini untuk mengetahui implementasi pelaksanaan pembelajaran fiqih di DTA Al-Inshof dalam meningkatkan motifasi sholat berjamaah siswa. Berdasarkan analisa data hasil penelitian dapat diketahui bahwa terdapat korelasi positif yang signifikan antara pembelajaran fiqih dengan peningkatan pelaksanaan shalat fardu siswa di DTA Al-Inshof Cibadak.Dalam penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif deskriptif, melalui pengumpulan data dengan wawancara dan dengan observasi langsung ke lapangan untuk mendapatkan data dan fakta yang valid. Pelaksanaan pembelajaran fiqih yang diselenggarakan oleh DTA Al-Inshof Cibadak, memiliki impliksi positif yang cukup besar terhadap motifvasi sholat berjamaah siswa-siswi DTA.  Di sisi lain DTA Al-Inshof Cibadak memiliki langkah yang di ambil untuk mendukung pembelajaran fiqih dalam memotifasi siswa dalam pelaksanaan sholat berjama’ah sebagai berikut : Pertama, memberikan pembinaan dan pengawasan kepada guru supaya menguasai materi fiqih tentang bab sholat.    Kedua, mengawasi dan meriviw para siswa supaya mengetahui sejauhmana materi fiqih bab sholat diserap oleh mereka.  Ketiga, memberi contoh praktek ibadah sholat yang baik dan benar menurut aturan fiqih.   Keempat, melaksanakan sholat secara serempak baik oleh guru maupun oleh siswa.